Comparison of storage characteristics of ripe shelled pili (Canarium ovatum) kernels dried to three levels of moisture - Villamor, Cynthia A.
Moisture sorption studies were made on fresh ripe shelled pili kernels from tree #6 in UPLB Pili Drive. It showed the storage behavior of nuts when exposed to different relative humidity. Based on this result, 3 moisture levels were chosen as variable for the storage test of shelled pili kernels. To arrive at these moisture contents, 3 arbritrarily chosen temperatures were used in drying the unshelled pili nuts and their effect on the initial kernel quality was observed. It was found that unshelled pili nuts could be dried at temperatures of 30 deg, 50 deg, and 60 deg C without destroying the initial kernel quality. In storage test, another set of fresh pili nuts were dried using 50 deg C to 3 different moisture levels. The shelled kernel samples were packaged in a 3-layer laminate bag of low water-vapor-transmission-rate, stored and compared for their storage characteristics. It was found that pili samples having 4.13%, 1.79% and 1.31% moisture content (dry basis) were not very different in their storage behavior even after 126 days at 60 deg C. They were found to be not yet rancid. Likewise, all these 3 samples stored at 37 deg C for 44 days did not show prolific mold growth in acidified PDA medium. Moreover, no yeasts and molds appeared on the surface of these samples.